2007
DOI: 10.1073/pnas.0709704104
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus uses two distinct pathways to enter retinal pigmented epithelial cells

Abstract: Human cytomegalovirus infects multiple cell types, including fibroblasts and epithelial cells. It penetrates fibroblasts by fusion at the cell surface but is endocytosed into epithelial cells. In this report, we demonstrate by electron microscopy that the virus uses two different routes to enter retinal pigmented epithelial cells, depending on the cell type in which the infecting virus was produced. Virus produced in epithelial cells preferentially fuses with the plasma membrane, whereas fibroblast-derived vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 52 publications
5
74
2
Order By: Relevance
“…The derivation of HCMV may also influence receptor usage and routes of infection. Wang and Shenk (43) reported that HCMV produced by epithelial cells more extensively infected epithelial cells in the presence of lysosomotropic agents compared with HCMV derived from fibroblasts. However, anti-UL130 antibodies blocked epithelialderived and fibroblast-derived HCMV, suggesting that gH/gL/ UL128-131 was essential in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…The derivation of HCMV may also influence receptor usage and routes of infection. Wang and Shenk (43) reported that HCMV produced by epithelial cells more extensively infected epithelial cells in the presence of lysosomotropic agents compared with HCMV derived from fibroblasts. However, anti-UL130 antibodies blocked epithelialderived and fibroblast-derived HCMV, suggesting that gH/gL/ UL128-131 was essential in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pellets were fixed with prewarmed fixative (2.5% glutaraldehyde, 2% paraformaldehyde in sodium cacodylate) for 1 hour and processed. 20 Ultrathin sections were examined with a Jeol (Peabody, MA) JEM-1010 electron microscope fitted with an Advanced Microscopy Techniques (AMT) (Woburn, MA) digital camera with dedicated image acquisition software.…”
Section: Microarray Analysismentioning
confidence: 99%
“…As viral determinants for HCMV entry of EP, UL128L-encoded proteins, form a pentamer with gH and gL mediating HCMV entry into EP via an endocytotic pathway (Bodaghi et al, 1999;Ryckman et al, 2008;Wang & Shenk, 2005;Wang et al, 2007). The UL128L is conserved in RhCMV, and its products are postulated to form a pentamer complex with RhCMV gH and gL (Wussow et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins encoded by UL128L, together with glycoprotein H (gH) and L (gL), form a gH-anchored pentamer complex that mediates HCMV entry of EP and endothelial cells via receptor-dependent endocytosis. The genetic integrity of UL128L determines the level of virus entry, which, in turn, regulates the infectivity of HCMV in these cells (Bodaghi et al, 1999;Ryckman et al, 2006;Wang & Shenk, 2005;Wang et al, 2007). However, it has been noted that the anatomical and tissue origin of both EP and endothelial cells affects HCMV infection efficiency and pathogenesis (Esclatine et al, 2000;Fish et al, 1998;Jarvis & Nelson, 2007;Jarvis et al, 1999;Millard et al, 2010;Tugizov et al, 1996).…”
Section: Introductionmentioning
confidence: 99%